2007
DOI: 10.1007/s00011-006-6119-6
|View full text |Cite
|
Sign up to set email alerts
|

Modified skin window technique for the extended characterisation of acute inflammation in humans

Abstract: Objective-To modify the skin window technique for extended analysis of acute inflammatory responses in humans, and demonstrate its applicability for investigating disease.Subjects-15 healthy subjects and 5 Crohn's patients.Treatment-Skin windows, created by dermal abrasion, were overlaid for various durations with filter papers saturated in saline, 100 ng/ml muramyl dipeptide (MDP) or 10 μg/ml interleukin-8 (IL-8).Methods-Exuded leukocytes were analyzed by microscopy, immunoblot, DNA-bound transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The changes observed indicate an involvement of T cells (CD8a, CD3e, CD4), macrophages (CD68), monocytes (CD14) and PDCs (CLEC4C) in response to the tape stripping challenge in this study, whereas B cell (CD19) and neutrophil (MPO) marker gene expression did not change indicating no changes in these cell populations. Previous observations [7] have shown that neutrophils are the main infiltrating cells in exudates formed after tape stripping and that the proportions of neutrophils to other leukocytes decrease with time after challenge; therefore, as the measurement in our study was 22-24 h post challenge, neutrophil numbers would be expected to be decreasing and this might be reflected in the lack of transcriptional changes in MPO. Other studies have also identified an important role for innate immune cells in response to tape stripping and these changes were observed within the dermal compartment of the skin [14].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The changes observed indicate an involvement of T cells (CD8a, CD3e, CD4), macrophages (CD68), monocytes (CD14) and PDCs (CLEC4C) in response to the tape stripping challenge in this study, whereas B cell (CD19) and neutrophil (MPO) marker gene expression did not change indicating no changes in these cell populations. Previous observations [7] have shown that neutrophils are the main infiltrating cells in exudates formed after tape stripping and that the proportions of neutrophils to other leukocytes decrease with time after challenge; therefore, as the measurement in our study was 22-24 h post challenge, neutrophil numbers would be expected to be decreasing and this might be reflected in the lack of transcriptional changes in MPO. Other studies have also identified an important role for innate immune cells in response to tape stripping and these changes were observed within the dermal compartment of the skin [14].…”
Section: Discussionmentioning
confidence: 83%
“…There was no increase in TNF-a IL-8, IL-10 or TGF-a mRNAs in the dermal samples. More recently, Marks et al [7] collected cells from the exudates produced post tape stripping and described a predominantly neutrophilic influx after 6 h followed by monocyte infiltrate 24-48 h later. By 24 h a variety of cytokines including IL-8, IL-1b and to a lesser extent TNF-a were induced.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this complexity we were unable to identify abnormal PKC activity using isotype specific activation antibodies, but the inclusion of BIM, a non-selective PKC inhibitor provided some evidence to support their involvement. Furthermore, abnormal PKC activity has previously been identified in CD patients during acute inflammation[45]. Defective apoptosis and NADPH oxidase activity may result from abnormal PKC activity but equally it may depend on downstream events.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately 50% of patients with chronic granulomatous disease (which results from inherited primary immune deficiencies in neutrophil function) develop non-infectious chronic bowel inflammation that bears a striking resemblance to CD in clinical, endoscopic, and histopathological assessment [ 43 ]. Compared with healthy controls or patients with rheumatoid arthritis, the numbers of neutrophils that pass out of the skin windows created by dermal abrasion are lower in patients with Crohn’s disease [ 18 , 19 ]. This finding might be due to a deficient local inflammatory response [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the intrinsic functions of neutrophils (e.g., phagocytosis, bacterial killing and digestion) in CD are intact [ 15 , 16 , 17 ], but the recruitment of neutrophils is abnormal. Segal et al [ 18 ] and Marks et al [ 19 ] found that the number of neutrophils that pass out of a skin window created by dermal abrasion is considerably lower in patients with CD compared with healthy controls. As in these skin windows, a subsequent study found that there is a significant reduction in neutrophil recruitment at trauma sites in rectum and ileum of patients with CD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%